A Normative and Self-Organizing Piloting Model for Virtual Network Management - Valadares, Carolina; Netto, Manoel T. Abreu; Lucena, Carlos J. P. de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
The Internet has become an essential role in the society, serving every day billions of users spread all over the world. It is a complex network that holds an extensive range of services, applications and technologies. Its model, however, makes it difficult to solve structural problems such as management and maintaining. Network virtualization has been proposed to tackle this issue. In this paper, we use the concept of multi-agent system, norms and self-* properties to propose and validate an autonomic self-organizing model for virtual network management. As our proof-of-concept, we show that our system, which is composed of a virtual network of virtual machines capable of self-organizing themselves in a totally decentralized way across a physical infrastructure in order to cope with environment changes, satisfies its main goal of efficiently reorganize itself with no central control.